(3aJM GdCbaGd hVQH GdCeKGds - (3LeGd GdOjf CHh YHO Gddg eMeO Hf eMeO Hf YeQ GdMVQei HMQb Gdjefis ((3ehQjJGfjG s)
(3ChdgG (B:s
(3fGbU ef Chdg hjHOC GdehLhO ajg Hbhdg (B: (3hHYO aGdaYd ef jMce JUQa jMR ef GddZI GdCHhGH hGdSHdG s
(3BNQgG (B:s
(3fGbU hBNQ GdehLhO (B: (3GdeOgf ade jSeY ajgG ZjQ Gd Ve hCeG GdeOb aSeY ajg CjVkG GdeOb HcSQ Gdeje Ydi GdbjGS s
(3BKGQ QWhHI CJJ Ydi HYV CWQGagGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B397 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1536s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdUQas